2021
DOI: 10.1177/09722629211001985
|View full text |Cite
|
Sign up to set email alerts
|

Financial Performance and Gender Diversity: The Moderating and Mediating Effect of CSR Disclosure and Expenditure of Listed Firms in India

Abstract: The study examines the moderating and mediating effect of corporate social responsibility (CSR) disclosure and CSR expenditure on the association between listed firms’ financial performance and gender diversity. There are 80 listed firms with 800 firm-year observations from 2010 to 2019 that qualified for the study using the Indian stock market. The first finding shows a negative association between financial leverage and gender diversity. The second finding shows that the implementation of CSR disclosure hurt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
(112 reference statements)
0
6
0
1
Order By: Relevance
“…Bank Central Asia, Tbk., one of the companies on the Kompas 100 Index Issuer as the largest banking company in Indonesia was able to show optimal performance throughout 2021 so that stakeholders responded positively and the allocation of CSR became a priority. Research conducted by the references [35][36][37][38][39][40] state that CSR affects Stock Return.…”
Section: Discussionmentioning
confidence: 99%
“…Bank Central Asia, Tbk., one of the companies on the Kompas 100 Index Issuer as the largest banking company in Indonesia was able to show optimal performance throughout 2021 so that stakeholders responded positively and the allocation of CSR became a priority. Research conducted by the references [35][36][37][38][39][40] state that CSR affects Stock Return.…”
Section: Discussionmentioning
confidence: 99%
“…CSR expenditure is the amount invested by the company in corporate social activities. It is converted into a natural logarithm to remove outliers (Oware & Mallikarjunappa, 2021).…”
Section: Variables and Data Collectionmentioning
confidence: 99%
“…They have not investigated the CSR performance based on the Corporate Social Responsibility Expenditure value (in future CSRE). Previous studies have consistently demonstrated that a company's investment in CSR initiatives has a meaningful impact on its financial performance (Oware & Mallikarjunappa, 2021).…”
Section: Csr: Indian Contextmentioning
confidence: 99%
See 2 more Smart Citations